Red Corbusier in red Moscow (а coloristic sketch) - Zavadovsky, Petr (project baikal, 2026)
The article examines the change in the color of the cladding of Le Corbusier’s Centrosoyuz building during its designing and the impact of this circumstance on the architectural practice in the Soviet avant-garde period of 1929–1935.
Keywords: constructivism; Le Corbusier; Centrosoyuz; Artik tuff